STATE ISSUE - THE CENTER OF “POLITICS” - Razakov Davron Khalikovich (Galaxy International Interdisciplinary Research Journal, 2021)
There are many genius thinkers in the history of the Eastern Renaissance whose name is imprinted on eternity. One of them is Abu Ali Hasan ibn Ali Tusi-Nizamulmulk (1018-1092), who served the kings in the Near and Middle East (1037-1194) for many years as an honest minister and rose to prominence. In the works of Nizamulmulk, such as “Siyasatnoma”, “Dastur-ul-vuzaro”, “Qanunul-mulk”, which served as a necessary guide for the rulers of the East several centuries before Niccolo Machiavelli, moral categories such as justice, fairness, correctness and honesty interpreted in connection with and strongly defended the idea of a strong state centralized. He promoted the idea that the king should be brave, wise, prudent, and determined. He considered the important role of officials (responsible personnel) in governing the state, their selection and placement at the level of a specific requirement. In particular, the “Policy” provides recommendations for the education, protection and, if necessary, punishment of officials, which attracts the attention of politicians and heads of state. Nizamulmulk states that if the centralized government (executive power) is strong in the state, then peace and justice will be stable in the state, the citizen (people) will achieve their goal, the society will live in peace and justice, mercy.